Suspensiones de células embriogénicas de banano y plátano - Srosse, H.; Domergue, R.; Panis, Bartholomeus; Escalant, J-V.; Côte, F.; Vézina, A.; Picq, C.; International Network for the Improvement of Banana and Plantain (2003)
This guideline presents two protocols to produce embryogenic cell suspensions by using scalps or immature male flowers. The protocols have been developed by the Laboratory of Tropical Crop Improvement of Katholieke Universiteit Leuven (KULeuven) and the cellular biology laboratory of the Centre de coopération internationale en recherche agronomique pour le développement (Cirad).